Anti-obesity Activity of Ethanol Extract from Bitter Melon in Mice Fed High-Fat Diet - Ae Yoon, Nal (Dev Reprod, 2019)
In many cases, obesity is associated with metabolic disorders. Recently, natural compounds that may be beneficial for improving obesity have received increasing attention. Bitter melon has received attention as a diabetes treatment. NAD(+)-dependent deacetylase (Sirtuin 1, SIRT1) has emerged as a novel therapeutic target for metabolic diseases. In this study, ethanol extract of bitter melon (BME) suppressed adipocyte differentiation and significantly increased the expression of SIRT1 in fully differentiated 3T3-L1 cells. Moreover, it enhanced the activation of AMP-activated protein kinase (AMPK). In high-fat diet (HFD)-fed induced-obesity mice, BME suppressed HFD-induced increases in body weight and white adipose tissue (WAT) weight. BME also increased the expression of SIRT1 and suppressed peroxisome proliferator-activated receptor and sterol regulatory element binding protein 1 expressions of WAT from HFD-fed mice. These findings suggest that BME prevents obesity by activating the SIRT1 and AMPK pathway and that it may be a useful dietary supplement for preventing obesity.